Application of the AHP-TOPSIS Method to Support Stock Investment Decisions Based on Financial Ratio Analysis - Pardede, Ester; Susanti, Dwi; Sukono, Sukono (International Journal of Global Operations Research, 2023)
Stock is one form of investment that is currently popular, both for young people, parents, and industry. This can be seen from the increasing number of investors and companies listed on the Indonesia Stock Exchange (IDX). This makes investors confused in determining the best stock choices. Analysis of stock selection needs to be done before someone invest so that the selected stock does not lose and can generate optimal profits. This study discusses the recommendation for alternative stocks from the IDX30 index. The parameters for selecting alternative stocks considered include the criteria of Earning Per Share (EPS), Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). Then the weight of each criterion will be searched using the Analytical Hierarchy Process (AHP) method and sorted using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to produce stock recommendations from companies listed on the Indonesia Stock Exchange. The results showed that the Earning Per Share (EPS) criteria became the first priority with a weight of 0,2927, then Return on Equity (ROE) with a weight of 0,2728, followed by Net Profit Margin (NPM) with a weight of 0,2583, and Return on Assets (ROA) with a weight 0,1759. Then alternative results are obtained based on the preference value and ranking 14 companies that have a preference value above 0.5 and can be used as a consideration in making investment decisions, with BBCA as a priority alternative.